Pengaruh Intensitas dan Konsentrasi GA3 untuk Peningkatan Kualitas Buah Jeruk Siam (Citrus nobilis) Jember - Dinda Nurisma, Megy; FUROIDAH, NANIK (JURNAL AGROPLANT, 2024)
This study aims to determine the best intensity and concentration of ZPT GA3 to improve the quality of Siamese oranges. This research was conducted from November 2022 to April 2023, in Pancakarya Village, Ajung District, Jember Regency, East Java Province. This study used a randomized block design (RBD) with a factorial pattern, the first factor was 3 concentration treatments (K) and the second factor 3 intensity treatments (I), repeated 3 times. So that the total experiment is 27 plants. The treatment used was I1 = 1 spraying; I2 = 2 times spraying; I3 = 3 sprays and K1 = 20 ppm concentration; K2 = Concentration 40 ppm; K3 = Concentration 60 ppm. The test was carried out with the F-test with analysis of variance (ANOVA), if there is a significant difference (F-count value > F-table) then proceed with the 5% DMRT test. The results showed that the combination of using intensity 1 time per 2 weeks (I1) with a concentration of 40 ppm GA3 (K2) showed a significant interaction on fruit volume parameters. However, the difference was not significant in fruit weight.